Comparing the performance of different catalyst packings for Fischer-Tropsch synthesis - Mhinga, Masana (Department of Chemical Engineering, 2022)
The increase in global population accompanied by depleting fossil fuel reserves and rising fuel demand is prompting the need to increase and diversify fuel production rates. In addition, increasing global pressure to reduce the contribution of greenhouse gas emissions to global warming and as well as rising oil prices are driving efforts to improve efficiency and environmental sustainability of fuel production. Low temperature Fischer-Tropsch synthesis is an attractive alternative to crude refining. During Fischer-Tropsch synthesis (FTS), synthesis gas, a mixture of H2 and CO is converted to a wide range of value-added long chain hydrocarbon products in a polymerisation reaction: (2n+1) H2 + n CO → CnH2n+2 + n H2O -∆H= 165 − 214 kJ ∙ mol!" 0-1 The benefit of Fischer-Tropsch synthesis is that any carbonaceous feedstock can be used to generate synthesis gas, including natural gas, coal and biomass. However, exploitation of biomass requires decentralised, small-scale units, to reduce the complexity of a variable feed supply. To make this feasible, small-scale FT reactors must be simple to operate and achieve high single-pass conversion. Multi-tubular fixed-bed reactors are ideal for realising this as they are relatively easy to scale-up and operate when compared to other reactor technologies. However, conventional catalyst packings for fixed-bed reactors result in high pressure drop. Structured packings offer an attractive solution as their high porosity (ca. 70%-90%) when compared to that of conventional pellet- or particle packed beds (ca. 40%) results in significant reductions in pressure drop, which lowers gas compression costs. Large pellets are typically used in fixed-bed reactors to reduce pressure drop, resulting in increased internal diffusion limitations which may result in increased CH4 selectivity and reduced C5+ selectivity, the desired product. In contrast, a thin layer of the catalytically active material applied on the surface of the structured substrate results in lower diffusion limitations, and thus maintaining a favourable product distribution. Furthermore, open-cell foams reactors have the potential to enhance external mass in fixed-bed reactors because of their tortuous flow channels and high geometric surface area. The aim of this study was to compare the performance of catalyst coated on a ceramic open cell foam with that of catalyst powder, pellets and catalyst coated on a ceramic honeycomb monolith in terms of CO conversion, CH4 and C5+ productivity per gram catalyst using an alumina-supported catalyst containing 22 wt.% Co and 0.05 wt.% Pt. Furthermore, the effect of catalyst layer thickness on catalyst performance was also evaluated. It was shown that the pellets performed poorly when compared to the catalyst powder due to its much higher CO2 and CH4 selectivity, which were attributed to poor temperature control, induced by large diffusion length (i.e., pellet diameter). The foams and monoliths also performed poorly when compared to the catalyst powder. For monoliths and foams wash coated with ca. 0.5 g of catalyst, it was seen that CO conversion achieved was on average ca. 40% lower than that achieved over the catalyst powder at similar space velocities. The product selectivity was also poor. Furthermore, it was seen that despite the tortuous flow channels of the foams, which were initially thought to produce better mass transfer than the flat-wall channels of the monoliths, the performance of the foams was not better than that of the monoliths. Thus, it is concluded that the use of monoliths and foams does not improve performance in Fischer-Tropsch synthesis. The poor performance may be attributed to poor heat and mass transfer properties in the reactor set-up, and possibly aggravated by catalyst deactivation incurred during reactor startup.